KEBIJAKAN HUKUM PENGELOLAAN TANAH EKS HAK GUNA USAHA (HGU): STUDI EMPIRIS KONFLIK AGRARIA DI PT BSP - Bahmid Bahmid; Irda Pratiwi; Siti Hajar Siregar (Universitas Labuhanbatu, 2026)
This study examines the government’s legal policy in addressing the issue of unauthorized management of land formerly under Right to Cultivate (HGU) permits, with a case study focused on the ex-HGU land of PT. BSP. The main problem highlighted is the lack of legal certainty regarding the land’s status after the HGU permit expires, as well as the weak oversight by local governments over illegal land use by the public. This research employs an empirical method through interviews with relevant stakeholders and finds that limited local authority, overlapping regulations between central and regional governments, and the lack of accurate land data are the primary obstacles in resolving the issue. In addition, social factors such as historical land claims by communities and the lack of transparency in land information further complicate conflict resolution. Therefore, synergy between central and regional governments, agrarian policy reform, and the strengthening of institutional capacity and a transparent land information system are necessary to promote agrarian justice and legal certainty.Keywords: Ex-HGU Land, Legal Policy, Agrarian Conflict, PT. BSP, Legal Certainty